Faktor - Faktor Yang Berhubungan Dengan Kejadian Guillain-Barré Syndrome (GBS) : Literatur Review - Aulia Nur Fadilah; Fitriyani, Fitriyani; Suharmanto, Suharmanto (Medula, 2025)
Guillain-Barré Syndrome (GBS) is an acute neurological disease characterized by progressive muscle weakness, accompanied by decreased or loss of reflexes due to an autoimmune process that attacks the peripheral nervous system. This condition can progress rapidly and potentially lead to paralysis and even respiratory failure if not treated promptly. This literature review aims to identify and analyze factors associated with the occurrence of Guillain-Barré Syndrome based on recent research. The research method was conducted through a literature review using Google Scholar and PubMed databases using the keywords "Guillain-Barré Syndrome" and "factors." The articles retrieved were published between 2015 and 2025. Of the 45 articles found, only 17 met the inclusion criteria and were subjected to in-depth analysis. The analysis process involved a systematic review of research results, interpretation of findings, and drawing conclusions regarding risk factors and mechanisms involved in GBS. The study results indicate that bacterial or viral infections are the primary triggers for GBS, particularly Campylobacter jejuni, Epstein-Barr virus, Cytomegalovirus, and Zika virus. Furthermore, some cases have been linked to vaccinations, surgical procedures, autoimmune conditions, and a history of upper respiratory or gastrointestinal infections prior to the onset of neurological symptoms. Genetic factors and an abnormal immune response are also suspected to play a role in the pathogenesis of GBS. Understanding these factors is crucial for increasing clinical awareness, accelerating early diagnosis, and optimizing prevention and management strategies. Surveillance of infectious diseases, implementation of safe medical practices, and increased awareness among healthcare workers are expected to reduce the incidence and mortality from Guillain-Barré Syndrome. However, in Indonesia, integrated studies related to GBS factors are still limited. Therefore, this study is expected to contribute scientifically to control efforts and improve the quality of healthcare services for patients at risk for or diagnosed with Guillain-Barré Syndrome.